Polychaete fauna from the intertidal zone of the Kneiss Islands (central Mediterranean Sea) - MOSBAHI, N.; DAUVIN, J.C.; NEIFAR, L. (Mediterranean Marine Science, 2017)
The spatial and temporal distribution, abundance and assemblage structure of polychaete communities in the Kneiss Islands (central Mediterranean Sea) was studied at 42 stations selected among seagrass Zostera (Zosterella) noltei Hornemann meadows and unvegetated habitats sampled from April 2014 to January 2015. The Kneiss Islands represent a site of international interest in terms of their ornithological diversity (Important Bird Area, Ramsar Site and SPAMI). A total of 18,026 individuals and 92 species of polychaetes belonging to 25 families were identified. Analysis of the trophic structure reveals that the majority of stations are strongly dominated by deposit feeders (51.2%), followed by carnivores (34.8%) and suspension feeders (14%). Polychaete diversity and abundance were higher on the vegetated stations. Four polychaete assemblages are identified using MDS analysis. The distribution of polychaete assemblages are influenced by edaphic factors, particularly sediment structure and organic matter content. Seasonal variations of the polychaete community patterns at 20 stations show a maximum abundance and diversity during spring and summer and a minimum during winter. Seasonal fluctuations follow the seasonal variations of the environmental factors such as temperature and salinity, and correspond also to the lifestyle of the dominant species.